PRO Hair Safe Study: The Patient’s Perspective on the Effects of Scalp Cooling on Hair Preservation - Brunner C; Egle D; Ritter M; Kofler R; Giesinger JM; Schneitter L; Sztankay M; Emmelheinz M; Abdel Azim S; Wieser V; Oberguggenberger A (Breast Cancer: Targets and Therapy, 2023)
Christine Brunner,1 Daniel Egle,1 Magdalena Ritter,1 Ricarda Kofler,1 Johannes M Giesinger,2 Lisa Schneitter,1 Monika Sztankay,2 Miriam Emmelheinz,1 Samira Abdel Azim,1 Verena Wieser,1 Anne Oberguggenberger2 1Department of Gynecology and Obstetrics, Medical University of Innsbruck, Innsbruck, Austria; 2Department of Psychiatry, Psychotherapy, Psychosomatics and Medical Psychology, Psychiatry II, Medical University of Innsbruck, Innsbruck, AustriaCorrespondence: Christine Brunner, Department of Gynecology and Obstetrics, Medical University of Innsbruck, Anichstraße 35, Innsbruck, 6020, Austria, Tel +43 512 504 81194, Email c.brunner@tirol-kliniken.atPurpose: Alopecia has been reported a distressing side-effect of chemotherapy for breast cancer patients (BCP) that is highly relevant for quality of life during treatment. For the prevention of chemotherapy-induced alopecia, scalp cooling (SC) has been reported to be an effective and safe intervention. However, data on the patient’s perspective on effectiveness and applicability of SC in a clinical routine setting are scarce. In this comparative study, we aimed at a longitudinal assessment of patient-reported outcome (PRO) data on the effect of SC on alopecia and its effect on symptoms and functional health when applied in clinical routine in BCP receiving taxane or anthracycline-based chemotherapy.Patients and Methods: Study participants were allocated either to the intervention group receiving SC or to the control group based on patient preference (non-randomized study). All patients completed PRO-measures on hair preservation (EORTC Item Library items on hair loss), symptom and functional health measures (EORTC QLQ-C30 and -BR23) and the Body Image Scale (BIS). Outcomes were assessed at chemotherapy start (baseline), mid-chemotherapy, last chemotherapy cycle, 3 months follow-up and 6– 9 months follow-up.Results: Overall, we included 113 patients: 75 patients underwent SC (mean age = 51.3 years, 52.7% premenopausal); 38 patients standard care (mean age = 55.6 years, 39.5% premenopausal). A total of 53 patients (70.7%) discontinued SC, with 39 patients (73.5%) stating alopecia as the primary reason. On average, BCP stayed on treatment with the cooling cap for 40.2% of the duration of their chemotherapy (SD 25.3%). In an intention-to-treat analysis, we found no difference between the SC group and the control group with regard to their patient-reported hair loss (p=0.831) across the observation period, overall QOL (p=0.627), emotional functioning (p=0.737), social functioning (p=0.635) and body image (p=0.463) did not differ between groups.Conclusion: We found a high rate of SC-decliners and no beneficial effects of SC for patient-reported hair loss, symptoms and functional health. The efficacy and tolerability of SC applied in a clinical routine setting hence appeared to be limited. The further determination and up-front definition of criteria prognostic for effectiveness of SC may be helpful to identify patient subgroups that may experience a treatment benefit.Keywords: cooling cap, self-report, alopecia, chemotherapy